Immunoadjuvant potential of Azadirachta indica, Butea frondosa and Ficus religiosa against Swine flu vaccine antigen - Shubham S Gaikwad; Amit Gupta; Bharat Shinde (Shahrekord University of Medical Sciences, 2017)
Introduction: In general, primary or secondary metabolites derived from medicinal plant products might be responsible for stimulating or suppressing the immune system against specific protein antigens. The objective of this study was to evaluate the adjuvant potential of aqueous leaves extract of Azadirachta indica, Butea frondosa and Ficus religiosa against Swine flu vaccine antigen. Methods: In this study, our group evaluated the antibody (IgG) titre of Swine flu vaccine antigen (2 μg/mL) using variable doses (0.625-5 mg) of aqueous leaves extract of A. indica, B. frondosa and F. religiosa. In addition, Swiss mice were immunized subcutaneously (100 μL) on day 0 with Swine flu vaccine antigen (1:1000 dilution). Splenocytes were collected on day 7 and cultured with variable doses of aqueous leaves extract of A. indica, B. frondosa and F. religiosa pertaining to determine the total cellular content and splenocyte proliferation (Swine flu vaccine; Ovalbumin, OVA and Con A) assay. In addition, estimation of Th1 (IFN-gamma and TNF alpha) cytokines in cell culture supernatant containing swine flu vaccine antigen along with aqueous leaves extract were measured. Results: Aqueous leaves extract of A. indica, B. frondosa and F. religiosa showed anti-Swine flu titre at higher doses. In ex vivo animal model studies these three medicinal plants in the form of aqueous leaves extract enhanced total cellular content at higher doses but increased in splenocyte proliferation (Swine flu vaccine, OVA and Con A) assay at lower doses. Similarly, there was enhancement in Th1 cytokines (IFN-gamma, TNF alpha) with respect to swine flu vaccine antigen containing aqueous extract at lower doses as compared to control group. Conclusion: Aqueous leaves extract of A. indica, B. frondosa and F. religiosa showed adjuvant activity against Swine flu vaccine antigen and might be used in manufacturing active adjuvant for vaccine antigen.